PEMBUATAN PUPUK PADAT DARI HASIL SAMPING BIOGAS DI GUNUNGKIDUL - Anggita Sari Praharasti; Andi Febrisiantosa; Tri Hadi Jatmiko; Satriyo Krido Wahono; Dwi Joko Prasetyo; Diah Pratiwi; Ria Suryani; Wahyu Anggo Rizal; Nana Hidayat; Andri Suwanto (Jurnal Penelitian Pertanian Terapan, 2023)
Utilization of biogas by-products is expected to increase the beneficial aspects of the existence of a biogas reactor as a source of input for small-scale agriculture, despite the main function as a renewable energy supply. In this study, formulation of solid fertilizer from biogas solid waste and evaluation of formulation yields have been done. Solid (sludge) waste from the biogas reactor were separated and mixed with another biomass for further processing into fertilizer or nutrients for plants. Two formulations have been made (3 kg each) with treatments of one week fermentation with once back stirring (P1) and two weeks fermentation with twice back stirring (P2) aimed to identify the difference between the two samples based on the quality of solid fertilizers produced. The evaluation tests were pH, water content, C-organic, C/N ratio, by-products substance, NPK total, Fe total, and Zn total. The data were analyzed statistically using independent t-test Parametric Statistic for normally distributed and/or homogeny data and also Mann Whitney Non-Parametric Statistic for the opposite. The test results of the fertilizer formula showed a pH value of around 6-7 with water content value of 52-67%. C-Organic value resulted was 25.89±3.10 (P1) and 21.35±1.99 (P2). The resulting C/N ratio was 25,89±3.10 (P1) and 21.35±1.99 (P2). By-products substances, NPK total, Fe total, and Zn total parameter were in accordance with the quality standard of solid fertilizer. Further development efforts are needed to adjust the moisture content of the developed formulation. Moisture content was estimated to affect shelf life, in relation to the number of live microbes as a quality control.